1986
DOI: 10.1152/ajpheart.1986.251.1.h86
|View full text |Cite
|
Sign up to set email alerts
|

Sympathomimetic pressor responses to thyrotropin-releasing hormone in rats

Abstract: Cardiovascular responses to centrally administered thyrotropin-releasing hormone (TRH) were studied in urethan-anesthetized rats to allow continuous recording of attendant changes in sympathetic nerve activity. Intracerebroventricular infusions of TRH (0.05-5.0 micrograms) consistently increased not only blood pressure and heart rate, but also spike frequency in splanchnic, renal, or cervical sympathetic nerves. Parasympathetic inhibition seemed unlikely because TRH responses were unaltered by cholinergic bloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
1

Year Published

1987
1987
2002
2002

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 0 publications
2
20
1
Order By: Relevance
“…Indeed, when efferent sympathetic nerve activity was directly monitared in the anesthetized rat, TRH increased sympathetic outflow by 200%, even at a dose (2.4 pmol) that had no significant hemodynamic effects in the anesthetized rat. Again, our present data were weil in agreement with the previous sturlies in which icv TRH produced elevations in the circulating Ievels of catecholamines (26) and increased efferent sympathetic nerve activity in the renal and splanchnic sympathetic nerves (16,17). Furthermore, the hemodynamic responses to icv TRH were also effectively blocked by ganglionic blockers, adrenolytic drugs, and adrenergic antagonists (16,17,26), whereas hypophysectomy, thyroidectomy, or treatment with arginine vasopressin or angiotensin antagonists did not abolish the TRH responses (3,16,17,26).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Indeed, when efferent sympathetic nerve activity was directly monitared in the anesthetized rat, TRH increased sympathetic outflow by 200%, even at a dose (2.4 pmol) that had no significant hemodynamic effects in the anesthetized rat. Again, our present data were weil in agreement with the previous sturlies in which icv TRH produced elevations in the circulating Ievels of catecholamines (26) and increased efferent sympathetic nerve activity in the renal and splanchnic sympathetic nerves (16,17). Furthermore, the hemodynamic responses to icv TRH were also effectively blocked by ganglionic blockers, adrenolytic drugs, and adrenergic antagonists (16,17,26), whereas hypophysectomy, thyroidectomy, or treatment with arginine vasopressin or angiotensin antagonists did not abolish the TRH responses (3,16,17,26).…”
Section: Discussionsupporting
confidence: 92%
“…Pressor and tachycardic responses were also reported after icv infusion of TRH at picomole doses in halothane-anesthetized rats (5), whereas, in the urethane-anesthetized rat, significant increments in blood pressure were seen only after nanomole doses of TRH, and the onset of the TRH effects in the urethane-anesthetized rat was significantly slower; the maximum responses were observed 15 min after the administration of TRH and were sustained for 30 min (16,17). Interestingly, similar sustained pressor responses with slow onset were recently reported after injections of nanomale doses of TRH into the dorsal raphe nucleus (18).…”
Section: Discussionmentioning
confidence: 96%
“…9 This effect was blocked by the destruction of the sympathetic system, indicating that the pressor effect could be mediated by catecholamines involving the modulations of diverse neurotransmitter system activities. 16 Leptin gene expression and secretion are nutritionally as well as hormonally regulated; they are increased by overfeeding, high-fat diet, insulin, and glucocorticoids, and they are decreased by fasting and cathecolamines. 17,18 Therefore, it is tempting to speculate with regard to whether a reciprocal interaction exists between periventricular TRH and leptin levels mediated by the sympathetic outflow.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in progress in our laboratory have shown that in the conscious rat systemic administration of a high dose of TRH (2 mg/kg) induced a statistically significant rise in plasma vasopressin, but the magnitude of this increase was below the Ievels at which vasopressin can induce changes in blood pressure (7]. Pretreatment of urethane-anesthetized rats with a vasopressin antagonist failed to block the cardiovascular actions of ICV administered TRH [37]. The involvement of the other pressor system, the renin-angiotensin system, in the hypertensive effect of TRH seems also likely, since TRH has no effect on plasma renin activity in either the conscious rat (own unpublished observations) or in man [39].…”
Section: Other Possible Mediators Of the Trh Effectmentioning
confidence: 99%